Invited review. Natural rubber nanocomposites - Chuong, Bui; Tung, Nguyen Huy; Hung, Dang Viet; Duy Linh, Nguyen Pham (Vietnam Journal of Chemistry, 2017)
Natural rubber (NR) is a valuable and important polymer material that has wide and various applications. Therefore the investigations for NR improvement, particularly for special applications are in continuous development. In this trend, preparation of NR nanocomposites using nanofillers of both organic and inorganic origination is one of leading directions. In this paper, NR nanocomposites with the most popular and promising nanofillers were reviewed. These nanofillers are nanosilica and layered silicate as the most important fillers for NR industry after carbon black, and nanocellulose as a new abundant and environmental friendly filler. Methods of NR nanocomposites preparation were briefly summarized. The main attention was paid to the establishment of nanostructures in NR composites. Based on limited (about 80) references, mostly in recent 15 years, the improvement of NR nanocomposite properties was analyzed in connection with their nanostructure. Keywords. Natural rubber, nanocellulose, nanosilica, nanoclay, nanocomposite.